2018
DOI: 10.1007/s12325-018-0755-4
|View full text |Cite
|
Sign up to set email alerts
|

12-Month Outcomes of Goniotomy Performed Using the Kahook Dual Blade Combined with Cataract Surgery in Eyes with Medically Treated Glaucoma

Abstract: IntroductionTo describe the 12-month efficacy and safety of goniotomy performed using the Kahook Dual Blade (KDB) in combination with cataract surgery in eyes with medically treated open-angle glaucoma (OAG).MethodsThis was a prospective, interventional case series conducted at seven centers in North America. Consecutive patients with medically treated OAG and visually significant cataract underwent phacoemulsification combined with goniotomy (PE + goniotomy) using KDB. Indications for glaucoma surgery include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
99
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 17 publications
11
99
5
Order By: Relevance
“…Overall, combined KDB plus cataract surgery has a great decrease in IOP measurement postoperatively. This finding again confirms the finding by Dorairaj (2018), which emphasizes the effectiveness of surgery in the reduction of IOP [7]. As evidenced in the findings of the present study, IOP reduced with time since surgery [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, combined KDB plus cataract surgery has a great decrease in IOP measurement postoperatively. This finding again confirms the finding by Dorairaj (2018), which emphasizes the effectiveness of surgery in the reduction of IOP [7]. As evidenced in the findings of the present study, IOP reduced with time since surgery [8].…”
Section: Discussionsupporting
confidence: 92%
“…Also, in the KDB only group, the decrease in the number of medications used was significant (P-value=0.00). This finding was also the same in the study by Dorairaj (2018), where they emphasized that the method with the greatest effectiveness to reduce IOP was surgery [7]. However, the method also gives rise to other complications.…”
Section: Discussionsupporting
confidence: 72%
“…Most of the studies lasted for at least 1 year, with 26 (30%) lasting for 2 or more years. Many of the technologies and surgical techniques were each described by a small number of prospective studies ( Figure 1) including endocyclophotocoagulation (ECP), [7][8][9][10][11] MicroPulse, 12,13 Ultrasound-based procedures, 14,15 YAG gonio procedures, [16][17][18] micro trabecular procedures, [19][20][21][22][23] Diathermy-based procedures, 24,25 Excimer Laser, 26 Kahook Dual Blade (KDB), 27,28 Hydrus, [29][30][31] and CyPass. [32][33][34][35][36] iStent, Trabectome, and Xen had the highest number of prospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the KDB group as a standalone procedure recorded a 41.7% drop in mean IOP from baseline (17.25±7.45 to 12.67±1.15mmHg) while topical medications reduced by 1.25 (55.5%). This group has 50% of eyes with moderate-to-severe POAG.Dorairaj, et al in prospective study also multicenter reported mean IOP reduction from baseline of above 20% at 12 months[11]. Mean IOP decreased from 16.8±0.6 to 12.4±0.3 (p<0.001), a 26.2% reduction.…”
mentioning
confidence: 88%